Microstructural Characterization of Ti-6Al-7Nb Alloy After Severe Plastic Deformation - Gallego, Juno [UNESP]; Pinheiro, Tiago Santos; Valiev, Ruslan Zufarovich; Polyakova, Veronika; Bolfarini, Claudemiro; Kiminami, Claudio Shyinti; Jorge, Alberto Moreira; Botta, Walter Jose (Universidade Federal de São Carlos (UFSCar), Dept Engenharia Materials, 2012)
The ASTM F1295/Ti-6Al-7Nb alloy present mechanical properties and biocompatibility very attractive for application in medical and dental implants. In this context, processing of these Ti-based alloys by severe plastic deformation (SPD) has been extensively reported recently. However, the mechanical properties of equal channel angular pressed (ECAP) ASTM F1295 alloy are still a matter of research. In the present study, Ti-6Al-7Nb samples were processed by ECAP following thermomechanical processing which effects on the microstructure of Ti-6Al-7Nb alloy were investigated by X-ray diffraction (XRD) and transmission electron microscopy (TEM). The analyses have shown that the microstructure was composed by ultrafine grains (UFG) with sizes ranging from 200 to 400 nm. Ring-type selected area electron diffraction patterns (SAEDP) suggested the co-existence of low- and high-angle grain boundaries. Some regions of the samples have presented evidences of the presence of grains with unfavorable orientation to the plastic deformation. These grains can act as rigid bodies and concentrate the deformation in its surrounding areas, as an "open-die grain" mechanism. Such deformation mechanism could be attributed to the differences in the plastic behavior between the alpha and beta titanium phases.
Keywords: Ti-6Al-7Nb alloy; ECAP; ultra-fine grained microstructure; XRD; TEM